The Association of Economic Outcome and Geriatric Syndromes among Older Adults with Transcatheter Aortic Valve Replacement (TAVR) - Min Ji Kwak; Rafia Rasu; Robert O. Morgan; Jessica Lee; Nahid J. Rianon; Holly M. Holmes; Abhijeet Dhoble; Dae Hyun Kim (Journal of Health Economics and Outcomes Research)
**Background:** The association of geriatric syndromes and economic outcomes among patients who are undergoing transcatheter aortic valve replacement (TAVR) remains unknown.